(3GdeMGSHI GdeMhSHIs - (3MSGe(B, (3YhGOs ((3YeGf(B:s (3OGQ GdNdjL ddfTQ hGdJhRjY(B,s, 2014)
(3GdeMGSHI GdeMhSHI aj GdeDSSGJ GdJLGQjI , OhQI GdeTJQjGJ hGdeOahYGJ GdeMhSHI, OhQI GdeHjYGJ hGdebHhVGJ hGdJbGQjQ GdNJGejIs
Keywords: (3GdeMGSHIs; (3GdeMGSHI GdBdjIs; (3GdeMGSHI GdEdcJQhfjIs